HUBUNGAN ANTARA CURAH HUJAN DAN LUAS SERANGAN BELALANG KEMBARA (Locusta migratoria manilensis Meyen) DI PROVINSI LAMPUNG - Hamim Sudarsono; Rosma Hasibuan; I Gede Swibawa (Universitas Lampung, 2011)
Population outbreak of the oriental migratory locust, Locusta migratoria manilensis Meyen (Orthoptera: Aciridae), in Lampung between 1990’s to 2000’s has caused serious economic loss to agriculture. Anticipation of the pest outbreak is required to prevent serious loss in the future; one of possible approach is by analyzing data of rainfall and locust damage area. The study was aimed to analyze the relationship between rainfalls and area of damage caused by locust population in rice and corn fields using 17 years period of data from Lampung Province. The results indicate that locust damage occurred when there were high rainfalls followed low ones at wet season. Time lag of 8 month was determined as the period needed for L. migratoria manilensis to raise its population when the pest has developed gregarious colonies in the region. Rainfalls between 248,27 mm/month (on corn fields) to 287,06 mm/month (on rice fields) were optimum for the initiation of the locust population increase after a period of dry weather in the region. Results of autocorrelation tests indicate that the occurrence of locust damage in an area would be followed by population increase in a region where gregarious colonies have developed.